A three-dimensional transient model for heat transfer in thermoplastic composites during continuous resistance welding - Imad Zammar (Taylor & Francis Group, 2017)
The resistance welding technique for thermoplastic composites (TPCs) entails melting the TPC polymer at the joint interface using heat generated by resistive (Joule) heating of a conductive mesh or heating element placed between the surfaces to be welded. The continuous resistance welding (CRW) is an automated large-scale resistance welding technique that consists of a moving voltage source along the heating element creating a continuous weld along its path. This paper presents a transient model that is developed to predict the heat transfer in TPCs in all three dimensions during the CRW process. The model is finite element in nature and includes both the resistive and thermal conductivity behaviors of the material involved. The significance of this modeling approach is that it captures the movement of the electrical connection, as well as the nonuniform distribution of the current and resistive heating along the length and width of the weld seam. The modeling results are compared with experimental data obtained by thermocouples and an infrared camera, and exhibit solid conformance for predicting the trend of variations in weld temperature.